Kode Etik Guru Sebagai Bagian Dari Kemajuan Kompetensi Seorang Guru - Sarah Lestari Tampubolon; Unedo Sinaga; Tri Bayu Armanda; Dyna M T Pasaribu; Joy Prana Bangun; Jamaludin Jamaludin (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2024)
Teacher ethics, It refers to a set of moral and professional principles that govern the behavior of teachers in carrying out their duties and responsibilities. Teacher ethics includes aspects such as integrity, honesty, fairness, respect for diversity, and professional obligations towards students and their own profession. Indonesian Teacher Academic Qualification and Competency Standards are set by the government to ensure that teachers have the knowledge, skills and attitudes necessary to provide quality education. The standards cover various aspects, including minimum academic qualifications, teaching skills, communication skills, classroom management abilities, knowledge of curriculum, and understanding of student needs. The aim of this research is to find out how or to what extent a teacher's code of ethics is an indicator of the success of a teacher's competence who has at least 4 competencies.